1993
DOI: 10.1016/0044-8486(93)90295-a
|View full text |Cite
|
Sign up to set email alerts
|

Microflora associated with healthy and diseased turbot (Scophthalmus maximus) from three farms in northwest Spain

Abstract: A comparative analysis of the microbiological quality of three turbot (Scophthalnus maximus) farms (A, B, and C) located in Galicia (northwest Spain) is given. The microbial load and types of bacteria in the internal organs (liver and kidney) of apparently healthy fish was monitored over a year, and all the disease problems occurring during this survey were analyzed. The percentage of healthy turbot in which positive bacterial growth was obtained was relatively high in the three ongrowing facilities. Farm A ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 22 publications
4
52
0
1
Order By: Relevance
“…According Toranzo et al (1993) (Nishizawa et al, 2006) that was confirmed by recent survey of VHS in Turkey (Işıdan and Bolat, 2011). High level of diseased fish in BST stock could be related to combination of permanently acting stress environmental factors conjugated with different types of pollution, including chemical and organic agents; with permanent destruction of nursery, stock feeding and spawning grounds through different anthropogenic activities on the shelf and deep water environment; and thereafter permanent stress reducing its immune defense system and contamination by various pathogens (both bacterial or virus origin).…”
Section: Discussionsupporting
confidence: 53%
“…According Toranzo et al (1993) (Nishizawa et al, 2006) that was confirmed by recent survey of VHS in Turkey (Işıdan and Bolat, 2011). High level of diseased fish in BST stock could be related to combination of permanently acting stress environmental factors conjugated with different types of pollution, including chemical and organic agents; with permanent destruction of nursery, stock feeding and spawning grounds through different anthropogenic activities on the shelf and deep water environment; and thereafter permanent stress reducing its immune defense system and contamination by various pathogens (both bacterial or virus origin).…”
Section: Discussionsupporting
confidence: 53%
“…From these groups, Micrococcus and Lactobacillus were not detected in the water, of which, however, Flavobacterium strains were also isolated. The presence of these bacteria both in the aquatic environment and in the internal fish organs have been often observed (Sugita et al, 1985;Sakata, 1989;Toranzo et al, 1985Toranzo et al, , 1993Cahill, 1990). Aeromonas was the most abundant group in the fish, while, in global terms, the Gram-negative aerobic bacteria (specially Flavobacterium and Acinetobacter) were predominant in the water of the Congonhas River.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, the isolation of such bacteria from dying, farmed turbot Scophthalmus maximus was very uncommon until 1992 (Toranzo et al 1990(Toranzo et al , 1993a(Toranzo et al , 1994a; however, this situation now appears to be changing.…”
Section: Introductionmentioning
confidence: 99%